Effect of ICRF-193, a novel DNA topoisomerase II inhibitor, on simian virus 40 DNA and chromosome replication in vitro. - Ishimi, Y (1992)
The effect of ICRF-193, a noncleavable-complex-forming topoisomerase II inhibitor, on simian virus 40 (SV40) DNA and SV40 chromosome replication was examined by using an in vitro replication system composed of HeLa cell extracts and SV40 T antigen. Unlike the topoisomerase inhibitors VP-16 and camptothecin, ICRF-193 had little effect on DNA chain elongation during SV40 DNA replication, but high-molecular-weight DNAs instead of segregated monomer DNAs accumulated as major products. Analysis of the high-molecular-weight DNAs by two-dimensional gel electrophoresis revealed that they consisted of catenated dimers and late Cairns-type DNAs. Incubation of the replicated DNA with topoisomerase II resulted in conversion of the catenated dimers to monomer DNAs. These results indicate that ICRF-193 induces accumulation of catenated dimers and late Cairns-type DNAs by blocking the decatenating and relaxing activities of topoisomerase II in the late stage of SV40 DNA replication. In contrast, DNA replication of SV40 chromosomes was severely blocked by ICRF-193 at the late stage, and no catenated dimers were synthesized. These results are consistent with the finding that topoisomerase II is required for unwinding of the final duplex DNA in the late stage of SV40 chromosome replication in vitro.